Mixed Urinary Incontinence: Contemporary Perspectives on Pathophysiology, Diagnosis, and Evidence-Based Management for Nursing - Shrahli, Asma Ahmed; Abdullah Salem Abdullah Alammar,; May Ali Ahmed Alassadah Assir,; Meshael Alwrad Alrwuili,; Turki Ali Mohammed Alhuzaim ,; Fatimah Saad Alotaibi,; Reem Mohammad Alhumaidan,; Abdullah Nasser Alqumayzi,; Asia Omar Mohammed Abdullah,; Talal Houmod Ali Almutairi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mixed urinary incontinence (MUI), the co-occurrence of stress and urge incontinence, is a prevalent and burdensome condition, especially among older women. It significantly impairs quality of life, increases fall risk, and contributes to social isolation. The pathophysiology involves a complex interplay of pelvic floor weakness (causing stress leakage) and detrusor overactivity (causing urgency). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide contemporary nursing and clinical perspectives on the pathophysiology, diagnostic evaluation, and evidence-based management of MUI, emphasizing a stepwise, patient-centered approach. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive synthesis of current literature and guidelines from major urological and gynecological societies is presented. The review covers epidemiology, risk factors, and the diagnostic pathway, including history, physical exam, bladder diaries, cough stress test, and selective use of urodynamics. Both non-surgical and surgical management strategies are detailed. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evaluation begins with a detailed history, physical exam, urinalysis, and post-void residual measurement. First-line management is conservative, including bladder training, pelvic floor muscle therapy (e.g., the Knack technique), lifestyle modifications, and pharmacotherapy (e.g., antimuscarinics, mirabegron) for the urge component. For predominant stress incontinence refractory to conservative care, mid-urethral sling surgery is the standard, though pessaries, bulking agents, and adjustable devices are alternatives. Specialist referral is indicated for complex cases, surgical planning, or treatment failure. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective MUI management requires accurate diagnosis of the dominant component and a multimodal treatment plan initiated with conservative strategies. Successful outcomes depend on interprofessional collaboration, realistic patient expectations, and individualized care.